Customer Satisfaction Analysis Through Company Reputation, Customer Trust And Distribution Channels At PT Inti Palm Sumatra - Gultom, Pesta; Nainggolan, Elisabeth; Chandra, Surya (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The rapid growth of the palm oil industry in North Sumatra encourages companies to increase their competitiveness, one of which is through achieving customer satisfaction. This study aims to determine the effect of company reputation, customer trust, and distribution channels on customer satisfaction at PT Inti Palm Sumatra, both partially and simultaneously. The study was conducted quantitatively using a survey method through a questionnaire distributed to 46 customers of PT Inti Palm Sumatra in 2024, which were selected using a purposive sampling technique. Data analysis was carried out through validity and reliability tests, multiple linear regression, and t-tests and F-tests. The results of the study showed that partially, company reputation, customer trust, and distribution channels each had a significant effect on customer satisfaction. Simultaneously, the three variables were also proven to have a significant effect on customer satisfaction. Thus, all hypotheses in this study are accepted. These findings emphasize the importance of improving the company's image, building trust, and effective distribution arrangements as strategies to increase customer satisfaction and loyalty amidst increasingly fierce business competition.